2017
DOI: 10.21037/jgo.2017.06.13
|View full text |Cite
|
Sign up to set email alerts
|

Age and factors associated with access and time to post-operative adjuvant chemotherapy in colon cancer: a French epidemiological study

Abstract: Emergency colectomy, postoperative morbidities, and living alone are associated with increased time to AC. Organizational measures to reduce the time to AC are therefore unlikely to have an impact. In contrast, age is not associated with increased time to AC, but to access to AC. Reasons for omitting AC in older patients requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Cancer care quality also seems to be preserved at the continuity of care management moment, with both groups receiving appropriate and timely referrals to medical oncology. Current literature in this domain is limited, with one study at a tertiary care center corroborating our findings [ 8 ]; however, a French study of 24 regional hospitals found that emergency surgery was independently associated with longer time to receipt of adjuvant chemotherapy [ 18 ]. Several studies have also found an association between emergency surgery and non-receipt of adjuvant chemotherapy [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 75%
“…Cancer care quality also seems to be preserved at the continuity of care management moment, with both groups receiving appropriate and timely referrals to medical oncology. Current literature in this domain is limited, with one study at a tertiary care center corroborating our findings [ 8 ]; however, a French study of 24 regional hospitals found that emergency surgery was independently associated with longer time to receipt of adjuvant chemotherapy [ 18 ]. Several studies have also found an association between emergency surgery and non-receipt of adjuvant chemotherapy [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, genistein and luteolin could enhance the efficacy of chemotherapy. The adverse effect of genistein and luteolin on the long-term outcome of CRC patients without adjuvant chemotherapy may be due to the factors resulting in undertreatment, such as old age, comorbidities [26,27,28]. Indeed, elderly patients and those with a CVD history in this study had a higher level of genistein concentration.…”
Section: Discussionmentioning
confidence: 75%
“…Analyzing postoperative treatment, we found that the time to start adjuvant chemotherapy was similar between the emergency and elective group, suggesting that the recovery after surgery was not prolonged and the cancer work-up was not delayed. A French study with 404 patients reported a longer time to start adjuvant chemotherapy; however, other studies showed no delay [ 3 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%